EMBOLIZATION FOR HEMORRHAGE IN PATIENTS WITH BLADDER CANCER - S. A. Prozorov; S. A. Tarabarin; N. V. Kondratova; K. G. Mkrtchyan (Неотложная медицинская помощь)
Bladder or prostate bleeding is a frequent complication in patients with an inoperable tumor. The treatment of such patients remains a complex problem. Patients with massive hematuria are usually of elderly age and it is impossible to perform cystectomy in them. Embolization of bladder and prostate arteries is indicated for such patients. The aim of the article is to describe the role of embolization in the treatment of bleeding from the bladder and prostate where conservative therapy fails, and to analyze its effectiveness and risks. The advantage of intervention is minimal invasiveness and low blood loss.